Forward Exchange, Speculation, and the International Flow of Capital - Grubel, Herbert G. (Stanford, Calif., Stanford University Press, 1966)
This book analyzed forward exchange markets which improves on the existing theoretical work by synthesizing, reformulating, and extending various elements of traditional theory into a logically complete model.
Bibliography: p. [190]-192.
rua 12/06/17
Loans.
Keywords: Foreign exchange futures